Anticonvulsants and Bone Mineral Density - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The effect of carbamazepine and valproate monotherapy on bone mineral density was measured by dual-energy x-ray absorptiometry in 27 healthy children and 26 children with uncomplicated idiopathic epilepsy treated with an anticonvulsant for longer than 18 months at the Memorial University of Newfoundland, St John's, Canada.